2017
DOI: 10.1186/s12913-017-2524-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring attitudes and perceptions of patients and staff towards an after-hours co-pay clinic supplementing free HIV services in Kampala, Uganda

Abstract: BackgroundThere has been a rapid scale up of HIV services and access to anti-retroviral therapy in Africa over the last 10 years as a result of multilateral donor funding mechanisms. However, in order to continue to expand and to sustain these services it is important that “in country” options are explored. This study sought to explore attitudes and perceptions of people living with HIV (PLHIV) and health care staff towards using a fee-based “after hours” clinic (AHC) at the Infectious Diseases Institute (IDI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…This meant that one spent less time during the clinic visits and were able to attend to other personal activities. Previous studies have shown similar findings and describe the importance of patients spending less time in the clinic [ 42 , 43 ]. In addition, a sense of care and belonging was associated with receipt of regular communication on adherence and reminders about clinic appointments.…”
Section: Discussionsupporting
confidence: 71%
“…This meant that one spent less time during the clinic visits and were able to attend to other personal activities. Previous studies have shown similar findings and describe the importance of patients spending less time in the clinic [ 42 , 43 ]. In addition, a sense of care and belonging was associated with receipt of regular communication on adherence and reminders about clinic appointments.…”
Section: Discussionsupporting
confidence: 71%
“…These innovations have been key in diversifying funding away from a heavy dependence on traditional partners such as PEPFAR and The Global Fund [26]. These innovations include the introduction of ‘VIP’ or ‘Executive’ HIV clinics which cater to ‘higher-tier’ clients and accordingly charge higher service fees for upper middle class Ugandans in an after-hours clinic model implemented at the Infectious Diseases Institute (IDI) clinic in Kampala in November 2013 [48, 49]. The higher service charges for these ‘higher-tier’ recipients of care are then ploughed back to support poorer HIV patients [49].…”
Section: Resultsmentioning
confidence: 99%
“…These innovations include the introduction of ‘VIP’ or ‘Executive’ HIV clinics which cater to ‘higher-tier’ clients and accordingly charge higher service fees for upper middle class Ugandans in an after-hours clinic model implemented at the Infectious Diseases Institute (IDI) clinic in Kampala in November 2013 [48, 49]. The higher service charges for these ‘higher-tier’ recipients of care are then ploughed back to support poorer HIV patients [49]. Furthermore, a section of for-profit clinics in Uganda introduced a private ‘special HIV insurance’ scheme for patients that is based on a paid annual premium that offers ‘umbrella’ coverage for all HIV-associated costs for insured clients during the year [26].…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, calls for increasing country ownership of ART programs in Uganda and the broader Sub Saharan Africa region are warranted. Our study adds to calls for increased domestic spending on national HIV responses [ 3 , 7 ], leveraging the growth in Uganda’s middle class by co-opting them in contributing to meeting the costs of HIV treatment [ 2 , 53 ], introduction of innovative government levies to support HIV programs such as Uganda’s proposed AIDS Trust Fund to be financed through a levy on soft drinks [ 34 ]. Although numerous studies have focused on funding for ART scale-up from the perspective of GHIs [ 27 , 28 ] and at the level of domestic government level [ 29 , 30 ], our findings demonstrate that leadership at the level of ART-providing organizations plays a critical role in raising supplemental funding for ART programs thereby promoting long-term sustainability.…”
Section: Discussionmentioning
confidence: 99%